IMPLEMENTASI PEMBELAJARAN ONLINE MELALUI PEMANFAATAN GOOGLE CLASSROOM PADA PEMBELAJARAN IPS DALAM MENINGKATKAN PEMAHAMAN MATERI (Studi Deskriptif di SMPN 26 Bandung) - Firda Nurdiyanti, - (2020)
This research is motivated by the use of google classrooms as a learning tool as well as learning media in the implementation of e-learning in improving understanding of material on social studies learning during the Covid-19 pandemic. The implementation of e-learning through the use of google classroom is carried out in order to help teachers and students as alternative media providers for the implementation of e-learning during the distance learning period in social studies learning. The purpose of this study was to describe the implementation of e-learning through the use of google classroom in improving students' understanding of material in social studies learning. This research is a qualitative descriptive study in class VIII Junior High School 26 Bandung. Data collection techniques are carried out through interviews, observation, and documentation study. The results of the researcher's findings show that through the use of google classroom conducted by the teacher during the implementation of distance learning in improving understanding of social studies subjects, this is quite good. This is shown in the google classroom google classroom feature which is used during the learning process by the teacher, namely; 1) virtual classrooms that provide social studies learning spaces in class, namely class VIII A-VIII F; 2) communication (communication) helps teachers and students learn and communicate without being limited by space and time; 3) assignment (assignment) helps the teacher in giving assignments and assessments as well as students in accessing assignments and collecting them. The conclusions from the results of this study. The implementation of online learning by utilizing Google Classroom in social studies learning in increasing understanding of the material goes quite well with the various conveniences felt by students and teachers. Although, its implementation has not run optimally due to several factors faced by teachers and students.